1980
DOI: 10.1111/j.1748-1716.1980.tb06567.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of spermatozoal zinc as temporary inhibitor of sperm nuclear chromatin decondensation ability in man

Abstract: Nuclear chromatin decondensation (NCD) of ejaculated human spermatozoa was studied in vitro. Spermatozoa subjected to membrane disintegration induced by the detergent sodium dodecyl sulphate (SDS) were found to undergo NCD if previously or afterwards treated with substances known to deplete the spermatozoa of zinc (albumin and EDTA). Zn2+, but not other, "prostatic" cations (Ca2+, Mg2+), inhibited the experimentally induced NCD and the NCD of spermatozoa from men with impaired prostatic function. It is suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
1
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 16 publications
0
58
1
1
Order By: Relevance
“…Since albumin does not cleave disulfide bridges, and in the meantime does decondense sperm [31], it seems that zinc depletion unmasks free thiols which would, in turn, destabilize the S-S bridges, provoking the decondensation of the nucleus [33]. The role of these free thiols, endogeneous within the sperm, seems to be ascer-*Deficient spermatogenesis [ 11 tained since thiol-blocking agents (copper, iodosobensoate, chloromercuribensoate, iodoacetamide) induce a 100% resistance to SDSiEDTA [32].…”
Section: Role Of Zincmentioning
confidence: 99%
See 3 more Smart Citations
“…Since albumin does not cleave disulfide bridges, and in the meantime does decondense sperm [31], it seems that zinc depletion unmasks free thiols which would, in turn, destabilize the S-S bridges, provoking the decondensation of the nucleus [33]. The role of these free thiols, endogeneous within the sperm, seems to be ascer-*Deficient spermatogenesis [ 11 tained since thiol-blocking agents (copper, iodosobensoate, chloromercuribensoate, iodoacetamide) induce a 100% resistance to SDSiEDTA [32].…”
Section: Role Of Zincmentioning
confidence: 99%
“…Normal seminal plasma stabilizes sperm depleted in zinc (341 or sperm from men with an impaired prostatic function, whereas calcium or magnesium have no such effect [31]. Zinc, but not calcium, inhibits the effects of heparin on the plasmatic membrane and the nucleus [37]; 80 pM zinc stabilizes 90% of sperm subjected to SDS [31]. Subjects with a low seminal zinc have a higher percentage of spontaneously decondensed sperm [22].…”
Section: Role Of Zincmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of high levels of Zn in the seminal plasma exerts adverse effects on spermatozoal motility and morphology [4, 131, on the preservation of intact cellular membranes [12], and on the stability of sperm nuclear chromatin structure [14, 151. Similarly, it has been shown that Zn ions adversely affect the morphology of the tail of the spermatozoa in bulls as well as in man [16].…”
mentioning
confidence: 99%